Development of pre-syrinx state and syringomyelia following a minor injury: a case report - Kleindienst, Andrea; Engelhorn, Tobias; Röckelein, Verena; Buchfelder, Michael (Journal of Medical Case Reports, 2020)
Background: A generally accepted rule is that posttraumatic syringomyelia (PTS) results from spinal cord injury (SCI). Case presentation: Here, we report the development of syringomyelia without SCI in a 54-year-old Caucasian man following a mild motor vehicle accident. The computed tomography on admission excluded an injury of the spine. Because of neck and back pain, magnetic resonance imaging was performed on day 3 post-injury and demonstrated minimal changes from a ligamentous strain at the cervicothoracic transition. Any traumatic affection of the bone, vertebral discs, intraspinal compartment, or spinal cord were excluded. Some limb weakness and neurogenic bladder dysfunction started manifesting within the following weeks. Repeated MRIs following the accident demonstrated arachnoid adhesions at the C1–2 level and spinal cord edema equivalent to a pre-syrinx state at 12 months and syrinx formation at 24 months. Because of further deterioration, decompression was performed at 36 months. Conclusions: We conclude that even after a minor trauma PTS can occur and that medullary edema (pre-syrinx state) may precede syrinx formation.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Pre-syrinx; Spinal cord injury; Syringomyelia; Trauma; Treatment